Clinical and radiographic success of pulpotomy with MTA in primary molars: 30 months follow up - Roza Haghgoo; Farid Abbasi (Iranian Association of Endodontists; Iranian Center for Endodontic Research, 2010)
Introduction: Pulpotomy of carious primary teeth with an exposed pulp is a common treatment option. Pulpotomy has been conducted with various medicaments over the years. The aim of this study was to evaluate clinical and radiographic success of primary vital pulpotomy with ProRoot and Root MTA. Materials and Methods: In this randomized clinical trial, children aged between 3-7 years who met the inclusion criteria were enrolled. A total of 70 teeth were deemed suitable under the inclusion criteria and teeth were randomly divided into the 2 groups; ProRoot and Root MTA. Pulpotomy was performed and immediately followed by coronal amalgam restoration. The clinical and radiographic follow ups were conducted 6, 12, 18, 30 months post-operatively. The data were analyzed using Exact Fisher test. Results: : At the final follow up, 28 teeth in ProRoot MTA and 26 teeth in Root MTA were evaluated. In the Root MTA group, 1 tooth had exfoliated and one had an abscess and furcal radiolucency radiographically. In ProRoot MTA group, external resorption was observed in 1 tooth. Statistical analysis did not show significant difference in success rate between 2 groups after 30 months. Conclusion: The success rates of Root and ProRoot MTA are similar, indicating that pulpotomy can be carried out successfully in both primary molars.